Books have their own fate…: Gregor, Ferenc: A szlovák nyelv magyar elemei [The Hungarian elements of the Slovak language]. Budapest, Kairosz Kiadó, 2023, pp. 953. ISBN: 978-963-514157-9 - Agyagási, Klára (Slavica, 2025)
Ferenc Gregor, the most prominent Hungarian researcher of the Slovak language, did not live to see the publication of his magnum opus. The present review has two goals: on the one hand, to commemorate an outstanding scholar who persevered on his own path in the pursuit of scholarly value, accepting all the difficulties of a lonely struggle, and whose efforts were crowned with success, albeit posthumously, thanks to the next generation of scholars; and, on the other hand, to draw attention to the significant linguistic and cultural influence that Hungarian dialects have had on the language of the Slovaks living in the northern region of the historical Kingdom of Hungary. This influence manifested itself in several waves and in several geographical regions and took on different thematic characteristics depending on the historical situation. Using a wide range of written sources, Ferenc Gregor identified nearly 1,000 Hungarian lexemes in the vocabulary of local variants of the Slovak language. Since Gregor accurately documented all cases where the Hungarian words in question also entered other Slavic languages of the Carpathian Basin, his work is significant not only for its outstanding value in contact linguistics, but also from an areal linguistic perspective.